Coleridge's Writings - Coleridge, Samuel Taylor. author. aut Link
XV, 253 p.
Keywords: This collection of Coleridge's political and social writings includes the second "Lay Sermon" of 1817 and "In the Constitution of Church and State", printed with only slight abridgements. It also has groups of briefer extracts tracing major steps in the development of Coleridge's mature thought.